Pengaruh Ketebalan Plastik Polyethylene densitas rendah terhadap Umur Simpan Bawang Daun (Allium fistulosum L.) - SARAGIH, HILDA ORITA; DHARMA, I PUTU; ASTAWA, I NYOMAN GEDE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.5, No.4, Oktober 2016, 2016)
Effect of Thickness Plastic Low Density Polyethylene to Shelf Live of union Left ( Allium fistulosum L . ) The research is to determine effect treatment of thickness polyethylene plastic and to determine level of thickness polyethylene plastic which are suitable against shelf life of left union. The Research conducted in Laboratory of Post-Harvest Technology Faculty of Agricultural Technology Udayana University in March 2016. The research used a completely randomized design (CRD) with five treatments, that are (P0) treatment control, (P1) the treatment use plastic thickness 0.02 mm, (P2) the treatment use plastic thickness 0.03 mm, (P3) the treatment use plastic thickness 0.04 mm and (P4) the treatment use plastic thickness 0.05 mm. The observation done for 5 days. The results showed that plastic thicknes of the polyethylene most real significant effect against change of the CO 2 concentration, weight loss, leaf chlorophyll and shelf life left union during storage at a temperature of 16 0 C. Treatment of polyethylene plastic packaging 0.04 mm (P3) shown to maintain the quality and extend the shelf life until 5 days with the characteristics of the stem and the leaves begin to wilt, yellow spots more and more 30%-40% on leaves and disability of 40%, compared with leek without treatment (P0) were only able to survive until 3 days with the characteristics increasingly withered stalks and leaves, the more yellow spots, the leaves yellow spots > 50% and dry leaves, defects of more than 50%.
Keywords: Union left, Plastic low polyethylene, and Shelf live